Analysis of drug pricing drivers under South Korea’s pharmaco-economic evaluation exemption policy (2015–2022) - Yu, Seung Rae; Lee, Jong Hyuk (Frontiers in Pharmacology, 2025)
ObjectiveThis study analysed the characteristics of new drugs listed under the pharmaco-economic evaluation exemption (PEE) system from 2015 to 2022 in South Korea and examined the factors influencing the pricing decisions under this system.MethodsA mixed-methods statistical approach was used to comprehensively evaluate the factors influencing drug pricing under PEE system. Descriptive statistics provide an overview of the dataset, while inferential statistics, including t-tests and Pearson’s correlation analyses, are used to explore variable associations. Multiple and hierarchical regression models identify and quantify the key determinants of drug prices, controlling for multicollinearity among the variables.ResultsFrom 2015 to 2022, 30 new drugs were listed under the PEE system. The average annual number of new drugs was four, but this figure significantly increased to eight in 2022. The “KOR/A7 lowest” variable exhibited a strong negative correlation with the budget impact variable (coefficient: 0.838, P < 0.001), indicating that drugs with higher budget impact tend to have lower prices compared to the A7 countrie’s lowest price.ConclusionSince the introduction of the PEE system in South Korea, patient access to new drugs has significantly improved. However, the rising expenditure on pharmaceuticals has made budget impact a significant consideration in pricing decisions, highlighting the need for ongoing monitoring of drug expenditure by payers. As the system evolves, enhanced oversight and policy adjustments will be crucial for balancing cost containment with equitable patient access. Developing tiered RSA models based on drug classification or therapeutic impact could be a viable approach to achieving this balance.